Dynamics of Na clusters in/on insulating substrates - Bär, Matthias; Faber, Bernd; Reinhard, Paul-Gerhard; Dinh, P. M.; Suraud, E.; Wopperer, P. (Journal of Physics: Conference Series, 2010)
We apply a hierarchical model for Na clusters in/on insulating substrate (Ar or MgO) to explore three different regimes of cluster dynamics. The effect of the interface is scrutinized for optical response of Na8 embedded in Ar matrix and deposited on MgO(001) surface. The different mechanical properties of Ar and MgO surface are explored in studying the collision with a Na6 cluster at different initial energies. The stabilization of highly charged Na clusters through a substrate is discussed for strong laser ionization of Na8 in Ar matrix and on MgO surface. © 2010 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24